AN INVESTIGATION OF MOTOR PERFORMANCE IN CHILDREN WITH JOINT HYPERMOBILITY: A PRELIMINARY STUDY - Akkaya, Kamile Uzun; Burak, Mustafa; Yildiz, Ayşe; Yıldız, Ramazan; Keleş, Müşerrefe Nur; Elbasan, Bülent (Gazi Üniversitesi, 2026)
Purpose: Children with joint hypermobility may experience problems such as motor delays, poor balance and coordination, clumsiness, frequent falls, and sensory disorders. The aim of this study was to evaluate the motor performance of children with joint hypermobility and compare it with that of children without hypermobility. Methods: Children aged between 4 and 18 years, with and without joint hypermobility, were included in the study. Joint hypermobility was assessed using the Beighton Scoring System. Motor performance was evaluated using the long form of the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition. Results: A total of 35 children (20 girls and 15 boys) participated in the study, including 15 with joint hypermobility and 20 without. The mean age of the participants was 12.8 ± 4.47 years. Subtests of the BOT-2, including fine motor control, manual coordination, body coordination, strength, and agility, as well as total motor proficiency scores, were found to be similar between the two groups (p>0.05). Conclusion: This preliminary study found that motor performance in children with and without joint hypermobility was comparable. Further studies involving a larger sample size are needed to support these findings.

Amaç: Eklem hipermobilitesi olan çocuklarda motor gecikmeler, zayıf denge ve koordinasyon, sakarlık, sık düşme, duyusal bozukluklar gibi problemler gözlenebilmektedir. Bu çalışmanın amacı, eklem hipermobilitesi olan çocukların motor performanslarını değerlendirmek ve eklem hipermobilitesi olmayan çocuklarla karşılaştırmaktır. Metod: Çalışmaya 4-18 yaş aralığında eklem hipermobilitesi olan ve olmayan çocuklar dahil edildi. Çocukların eklem hipermobilitesi Beighton Skorlaması ile belirlendikten sonra motor performansları Bruininks-Oseretsky Motor Yeterlik Testi-İkinci Basım (BOT-2) uzun formu ile değerlendirildi. Bulgular: Çalışmaya 15 eklem hipermobilitesi olan, 20 eklem hipermobilitesi olmayan toplam 35 çocuk (20 kız, 15 erkek) dâhil edildi. Çocukların yaş ortalaması 12.8 ± 4.47 yıldı. BOT-2’nin ince motor kontrol, el koordinasyonu, vücut koordinasyonu, kuvvet ve çeviklik alt testleri ile toplam motor yeterlilik değerleri her iki grupta da benzerdi (p>0.05). Sonuç: Yapılan bu ön çalışma ile eklem hipermobilitesi olan ve olmayan çocukların motor performanslarının benzer olduğu belirlendi. . Çalışmanın devamında daha fazla sayıda çocuğun değerlendirme sonuçlarının analiz edilmesine ihtiyaç vardır.
EKLEM HİPERMOBİLİTESİ OLAN ÇOCUKLARDA MOTOR PERFORMANSIN İNCELENMESİ: ÖN ÇALIŞMA
Keywords: Physiotherapy; Fizyoterapi